Enteric parasites and socio-epidemiological variables in an academic community - Souza Passos, Aldery; da Silva Santos, Raissa; dos Santos Andrade, Raoni; Ribeiro Santos Junior, Edemilton; Santos Bomfim, Erica; Sousa Ribeiro, Livia; Andrade dos Santos, Glauber; Araujo de Albuquerque, Wesley; Amor, Ana Lúcia Moreno (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
Studies linking human health to environmental conditions are essential since parasitic diseases are connected to environmental and sanitary aspects. This study identified the prevalence of enteric parasites in an academic community in the municipality of Santo Antônio de Jesus, Bahia, Brazil. The purpose was to determine the existence, or not, of links between infections and socio-epidemiological variables, such as personal hygiene habits, the presence of sewage systems and the environment. Participants answered a questionnaire and received universal collectors for fecal samples. Spontaneous sedimentation methods and Rugai were used for diagnosis. One hundred twenty-one samples were analyzed, in which a 38.8% parasite prevalence was detected as well as a 61.7% rate of monoparasitism, as well as a predominance of protozoa Endolimax nana (78.7%) and Giardia duodenalis (21.3%). Among parasitized individuals, 97.9% lived in the Recôncavo Baiano region. The following statistical significance stands out in the findings, with p<0.05: individuals who had already bathed in the local river were more likely to be parasitized than those who had not (p = 0.034) and individuals who washed their hands more frequently before meals proved to be less prone to intestinal parasitic infections (p = 0.018). Results evidenced the presence of enteric parasites in a number of participants in spite of their being university students. The socio-epidemiological variables analyzed brought to light characteristics that favor the establishment of the epidemiological infection triad, such as improper packaging of household waste on disposal and no records of regular domestic water tank cleaning. KEY WORDS: Enteric parasites; environment; diagnosis; health education.